The proposed engineering laboratory at the Kansas State Agricultural College - Lechner, Christian Dagobert (My University, 1899)
Introduction: After a great deal of labor, the Kansas State Agricultural College, as able to secure from the legislature of the state a fund which was sufficient to build a laboratory, but not large enough to supply it with the proper engineering laboratory equipments. When we consider what the true meaning of a laboratory is, its value cannot be overestimated, as a helper in developing the science with which it is connected. The science of engineering has grown upon experimental data, and hence it is necessary that there should be place equipped with expensive apparatus in order that the experimental side of the science may receive its proper attention and be carried out to proper satisfaction. If this is supplied, it not only furnishes a large field for the student, but also for the professor in charge, to carry out experiments and to make deeper research for facts, which will upbuild the science. All persons that have a fairly clear idea or understanding of science, are competent to understand such experiments, and to work at them until they get satisfactory results. The word laboratory is often misunderstood by some people.
Citation: Lechner, Christian Dagobert. The proposed engineering laboratory at the Kansas State Agricultural College. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Definititian of Terms; Wide Field for Development; Location; Theses; Manuscripts (documents)